The Talion law “tooth for a tooth”: self-defense as a motivation for shark bites on human aggressors - Clua, Eric E. G.; Vignaud, Thomas; Wirsing, Aaron J. (Frontiers in Conservation Science, 2025)
The concept of “self-defense,” based on aggression by one individual responding to an initial aggression by another, has been observed in several animal taxa such as birds and terrestrial mammals but never documented in detail in sharks. Based on a multi-decade study of the characteristics of shark bites on humans in French Polynesia Eastern-South Pacific, we show that certain human activities at sea, such as fishing and particularly underwater spearfishing and the management of passive fish traps, are associated with this type of bite. Following an initial agonistic behavior by a human on a shark, a pattern of self-defense bites ensues, characterized by immediate aggression in return. It is perpetrated without proportionality, often superficial with minimal tearing of flesh, and rarely fatal, except in special circumstances. During these interactions, the shark will sometimes respond to the initial anthropogenic stimulus with repeated bites. The motivation for these defensive bites can be distinguished from other drivers, such as the predation motivation on humans, which involves heavy loss of tissue. In the case of antipredation or fear motivation, when a shark anticipates a potential human aggression before it occurs, the attack is preceded by a characteristic agonistic behavior that is not present in the case of self-defense. The existence of this behavior cautions that attacks on sharks have the potential to trigger retaliatory bites and that untrained persons should never attempt to come to the rescue of a distressed shark, which may bite indiscriminately. Finally, we suggest that the media, which often sensationalizes these types of self-defense bites as attacks, could help to improve attitudes toward sharks and their conservation by more objectively reporting the culpability of humans in triggering them.